Speaking Test Apps Development: English Learning Enhancement in Online Learning Complexity - Putu Ayu Asty Senja Pratiwi; Takahashi Toshiaki (Makassar State University, 2023)
Abstract. This research tried to map the strength and weaknesses and evaluate the English teaching and learning processes in Balinese EFL learners during the online class. The use of IT in online learning has become a central issue for the decreasing of students’ motivation due to the lack of students – teachers’ interaction in the online class especially in English subject. The complexities in the online learning include how the use of IT can be synchronized with teaching and learning methods in delivering the learning material, how is the role of the teacher in motivating students, how to assess students' abilities in online learning, and many more. Those are the unavoidable obstacles faced by teachers and students during the online learning. This study was aimed at evaluating and making English online teaching and learning effective and creating IT-based application to optimized the teaching and learning process and the students’ performance. This qualitative research collects the data through observation , interviews and English speaking test to 15 students and six teachers. From the empirical studies of the Balinese EFL learners, the students stated that English learning in online classroom atmosphere were ineffective and unsupportive for their English skill development. The problems mainly arise from the lack of practice and interaction which caused a decrease in student motivation and interest in online learning. To be able to overcome those problems, the researcher created learning applications called Speaking Test App. and Teacher Speaking Test App. to facilitate teachers and students in learning process. This application can be freely accessed through the Playstore and Appstore. The students and teachers use the learning applications as interactive English learning mediums in the classrooms. The results of the study showed that with the technology-based learning media, the students' performance, enthusiasm and motivation in learning could be improved and highlight a significant impact for interaction in learning especially in English online learning.Keywords: English teaching and learning, IT-based learning, Online Learning